The hyperreality world of K-Pop alternate universe (AU) fanfiction writers on X - Faizah, Cholifah; Hidayat, Medhy Aginta (Digital Theory, Culture & Society, 2025)
This article explores how writers of K-Pop Alternate Universe (AU) fanfiction on the platform X (formerly Twitter) construct hyperreal worlds centered on homosexual relationships between male K-Pop idols. Within these AU fanfictions, writers creatively craft alternative realities where idols are portrayed as gay, often rendering these imagined worlds more vivid and detailed than the idols’ real lives. Using a qualitative method with a virtual presence phenomenology approach, the study reveals that AU writers employ various strategies—such as fake chats or tweets, images, videos, audio links, and character development—to build and sustain their hyperreal narratives. These strategies serve to both construct and reinforce the existence of homosexual AU fanfiction worlds. By leveraging social media as a storytelling platform, these writers not only produce but also amplify and disseminate their hyperreal creations, demonstrating the role of X as a powerful medium for expanding the reach and influence of fan-created realities.